A Privacy-Preserving Technique for Incremental Dataset on Cloud by Synthetic Data Perturbation - D, Vigneswari; Kumar N, Kumar; R.Lakshmi Tulasi, Dr (International Journal of Engineering and Technology, 2018)
Cloud is an impetus technology revolution, allowing data providers to store their privatized Electronic Health Record (EHR) for further analysis and outlook with a compromised privacy, where the shared data being exposed to various adversary attacks and malware threats. There are several masking and randomization techniques that provide hints of privacy. In this paper, the Electronic Health Record (EHR) values are perturbed using logarithmic data perturbation and outsourced to the cloud.Aims.To develop a privacy-preserving technique for effective sharing ofElectronic Health Record (EHR) on a cloud by logarithmic data perturbation.Methods.Synthetic logarithmic transformation is applied to the sensitive values in a record before they are outsourced and for better privacy.Results. Synthetic Logarithmic Transformation along with the incremental anonymization produces effective result compared to classical anonymization..Â